Findings of Condesing Osteitis in Remaining Roots of Lower Molar Tooth on Periapical Radiograph - Marsela Valiadanti; Nilasary Rochmanita Suparno (Sean Institute, 2025)
Introduction: Condensing osteitis is one of the lesions that is often found during dental radiographic examination. This lesion is associated with reactive osteoblast hyperplasia caused by dental pulp infection. If this infection continues, it can affect the vitality status of the teeth and make the teeth brittle, leaving behind residual tooth roots. Aim: to report condensing osteitis in the remaining roots of the lower molar teeth found through periapical radiography. Case and Management: A 22-year-old female patient came to RSGM Soelastri complaining of residual lower jaw tooth roots that made her uncomfortable when eating. There was no history of systemic disease or allergy history found. Based on the radiographic examination, there was a radiopaque lesion at the apex of the root of tooth 36 accompanied by loss of lamina dura and widening of the periodontal ligament. This case was diagnosed as radices of tooth 36 accompanied by condensing osteitis. The treatments given were extraction and medication which showed good healing results without complications. Conclusion: Condensing osteitis cases really require radiographic examination for accurate diagnosis and treatment, especially in cases involving residual tooth roots. This underlines the importance of a comprehensive diagnostic approach in dental practice to prevent potential infections and ensure optimal treatment outcomes.